Differential and Single-Ended Microstrip Lines Loaded with Slotted Magnetic-LC Resonators - J. Naqui; M. Durán-Sindreu; F. Martín (International Journal of Antennas and Propagation)
This paper is focused on magnetic-LC (MLC) resonators, namely, slotted resonators that can be considered the complementary counterparts of the so-called electric-LC (ELC) resonators. Both resonators exhibit two symmetry planes (i.e., they are bisymmetric), one of them being an electric wall and the other a magnetic wall at the fundamental resonance. Therefore, compared to other electrically small resonators such as folded stepped impedance resonators (SIRs), split ring resonators (SRRs), and their complementary counterparts, MLC and ELC resonators exhibit a very rich phenomenology. In this paper, single-ended microstrip lines and differential microstrip lines loaded with MLC resonators are studied, and potential applications are highlighted.